An identity-irrelevant discrimination task reveals familiarity-advantage in face perception and no self-advantage in voice perception - Tamaka Harada; Miyuki G. Kamachi; Yuko Yotsumoto (Acta Psychologica, 2024)
Whether or not self-face and self-voice are processed more accurately than others' remains inconclusive. Most previous studies asked participants to judge the presented stimulus as their own or as others', and compared response accuracy to discuss self-advantage. However, it is possible that participants responded correctly in the “other” trials not by identifying “other” but rather by rejecting “self.”The present study employed an identity-irrelevant discrimination task, in which participants detected the odd stimulus among the three sequentially presented stimuli. We measured the discrimination thresholds for the self, friend, and stranger conditions.In Experiment 1 (face), the discrimination thresholds for self and friends' faces were lower than those for strangers' faces. This suggests that self-face may not be perceived as special or unique, and facial representation may become more accurate due to increased familiarity through repetitive exposure. Whereas, in Experiment 2 (voice), the discrimination thresholds did not differ between the three conditions, suggesting that the sensitivity to changes is the same regardless of identity. Overall, we found no evidence for self-advantage in identification accuracy, as we observed a familiarity-advantage rather than self-advantage in face processing and a null difference in voice processing.